1997
DOI: 10.1007/bf01291887
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid levels of alpha-tocopherol (vitamin E) in Alzheimer's disease

Abstract: We compared CSF and serum levels, and the CST/serum ratio of alpha-tocopherol (vitamin E), measured by HPLC, in 44 apparently well-nourished patients with Alzheimer's disease (AD) and 37 matched controls. CSF and serum vitamin E levels were correlated, both in AD patients and in controls. The mean CSF and serum vitamin E levels were significantly lower in AD patients, and the CSF/serum ratio of AD patients did not differ significantly between the 2 study groups. CSF vitamin E levels did not correlate with age,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
2
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(52 citation statements)
references
References 37 publications
2
47
2
1
Order By: Relevance
“…In another study, damage induced by 3,4-methylene dioxy-methamphetmaine (MDMA) (20) and 1-methyl-4-phenyl-1,2,3,6-tetra hy dropyridine (21) to the serotoninergic and dopaminer gic nerve systems was prevented by vitamin C supple mentation. Besides these findings, vitamins E and C levels in the plasma (22) and cerebrospinal fluid of Alzheimer's pa tients (23) were lower than those in normal subjects.…”
mentioning
confidence: 78%
“…In another study, damage induced by 3,4-methylene dioxy-methamphetmaine (MDMA) (20) and 1-methyl-4-phenyl-1,2,3,6-tetra hy dropyridine (21) to the serotoninergic and dopaminer gic nerve systems was prevented by vitamin C supple mentation. Besides these findings, vitamins E and C levels in the plasma (22) and cerebrospinal fluid of Alzheimer's pa tients (23) were lower than those in normal subjects.…”
mentioning
confidence: 78%
“…For vitamin A, 5 [4][5][6][7][8] out of 6 [4][5][6][7][8]14] previous studies showed significantly higher prevalence of AD with lower levels. However, the studies on vitamin A and E and AD either did not adjust for confounders [5,6,9,12,14] or only adjusted for age and gender [4,7,8,10,11] or lipid levels [13] . Therefore, results of these studies are diffi cult to interpret since we showed that the association between vitamin A and E and prevalence of AD disappeared when adjustments were simultaneously made for age, gender and total cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…However, all these studies were performed in hospital-based populations. Furthermore, many studies did not adjust for confounders [5,6,9,12,14] , whereas those that did make adjustments [4,7,8,10,11,13] only corrected for either age, gender or cholesterol. However, these covariates as well as education and smoking may be important confounders.…”
Section: Introductionmentioning
confidence: 99%
“…Jeandel et al (1989) found that serum vitamin A concentrations were decreased in patients with AD. Similarly, other researchers have reported lower serum vitamin A concentrations in patients with AD (Zaman et al 1992;Jimenez-Jimenez et al 1997;Foy et al 1999;Bourdel-Marchasson et al 2001). Schippling et al (2000) reported lower plasma a-carotene levels but normal (3-carotene concentrations.…”
Section: Vitamin Amentioning
confidence: 99%